2011
DOI: 10.4021/jocmr630e
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Aspects of Human Brucellosis and Leptospirosis Outbreaks in Korea

Abstract: In order to compare the epidemiological aspects of human brucellosis (HB) and human leptospirosis (HL) outbreaks in Korea, we have analyzed the current state both of the disease incidence and related risk factors. A total 651 cases of HB occurred between 2001 and 2010 in Korea, and the average incidence rate per 100,000 populations was 0.15. A total 1,153 of HL cases occurred during the same period, and its rate was 0.24. While most of the HB prevalence occurred in the whole year round, prevalence in summer wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
19
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 3 publications
1
19
0
Order By: Relevance
“…B. abortus infection in elk, dog and Chinese water deer or B. canis infection in cattle (Baek et al, 2003(Baek et al, , 2012Her et al, 2010;Kang et al, 2011;Truong et al, 2011) have been reported. Of note, from 2002 to 2010, 651 human brucellosis cases were also reported to be associated with the livestock industry in Korea (Jang et al, 2011;Park et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…B. abortus infection in elk, dog and Chinese water deer or B. canis infection in cattle (Baek et al, 2003(Baek et al, , 2012Her et al, 2010;Kang et al, 2011;Truong et al, 2011) have been reported. Of note, from 2002 to 2010, 651 human brucellosis cases were also reported to be associated with the livestock industry in Korea (Jang et al, 2011;Park et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the AR was higher in summer than in other seasons (P º 0.05). This data strongly suggest that the incidence of brucellosis is influenced by climate, farm environmental conditions, epidemic patterns, and the characteristic traits of the disease strain (2,3,6,15). On the other hand, the BB and HB cases were geographically localized in the southeastern region of the Korean peninsula (42.5z of the total BB cases and 44.4z of the total HB cases) as compared to other areas ( P º 0.01).…”
mentioning
confidence: 77%
“…including Brucella melitensis, Brucella abortus, Brucella suis, and Brucella canis; moreover, marine mammal strains are known to be pathogenic agents in humans (1,2). In recent years, brucellosis has become a major zoonosis in Korea with a dramatic increase in incidence in domestic cattle and man (2)(3)(4)(6)(7)(8). Therefore, human brucellosis (HB) was classified as a type 3 notifiable disease by the Communicable Disease Prevention Act in August 2000 (6).…”
mentioning
confidence: 99%
See 2 more Smart Citations